Against Aesthetic Exceptionalism - De Boever, Arne (Forerunners: Ideas First, 2019)
Reconsiders exceptionalism between aesthetics and politics Here, Arne De Boever proposes the notion of aesthetic exceptionalism to describe the widespread belief that art and artists are exceptional. Against Aesthetic Exceptionalism challenges that belief by focusing on the sovereign artist as genius, as well as the original artwork as the foundation of the art market. Engaging with sculpture, conceptual artwork, and painting by emerging and established artists, De Boever proposes a worldly, democratic notion of unexceptional art as an antidote to the problems of aesthetic exceptionalism. Forerunners: Ideas First Short books of thought-in-process scholarship, where intense analysis, questioning, and speculation take the lead